Global analysis of the post-SNO solar neutrino data for standard and nonstandard oscillation mechanisms - Gago, A. M.; Guzzo, M. M.; de Holanda, P. C.; Nunokawa, H.; Nunokawa, H. [UNESP]; Peres, O. L.; Pleitez, V. [UNESP]; Zukanovich Funchal, R. (American Physical Society (APS), 2002)
What can we learn from solar neutrino observations? Is there any solution to the solar neutrino anomaly which is favored by the present experimental panorama? After SNO results, is it possible to affirm that neutrinos have mass? In order to answer such questions we analyze the current available data from the solar neutrino experiments, including the recent SNO result, in view of many acceptable solutions to the solar neutrino problem based on different conversion mechanisms, for the first time using the same statistical procedure. This allows us to do a direct comparison of the goodness of the fit among different solutions, from which we can discuss and conclude on the current status of each proposed dynamical mechanism. These solutions are based on different assumptions: (a) neutrino mass and mixing, (b) a nonvanishing neutrino magnetic moment, (c) the existence of nonstandard flavor-changing and nonuniversal neutrino interactions, and (d) a tiny violation of the equivalence principle. We investigate the quality of the fit provided by each one of these solutions not only to the total rate measured by all the solar neutrino experiments but also to the recoil electron energy spectrum measured at different zenith angles by the Super-Kamiokande Collaboration. We conclude that several nonstandard neutrino flavor conversion mechanisms provide a very good fit to the experimental data which is comparable with (or even slightly better than) the most famous solution to the solar neutrino anomaly based on the neutrino oscillation induced by mass.